Elastic and inelastic seismic response of buildings with damping systems - Ramirez, Oscar M.; Constantinou, Michael C.; Chrysostomou, Christis (My University, 2002)
The effect of damping on the response of elastic and inelastic single-degree-of-freedom systems was studied by nonlinear response-history analysis using earthquake histories that matched on average a 2000 NEHRP spectrum on a stiff soil site for a region of high seismic risk. New displacement reduction factors for levels of damping greater than 5% of critical are presented. New equations to relate inelastic and elastic displacements in the short-period range, for levels of damping greater than 5% of critical, are presented. The technical basis for reducing the minimum design base shear in damped buildings by a maximum of 25%, from that required for the corresponding undamped building, is derived based on comparable levels of damage in both the damped and undamped buildings.
Keywords: Damping (Mechanics); Earthquakes; Seismology